Indonesian Political System Post Reformation - Lailatul Berliana; Siti Nurhalizah; Nasya Amelia Putri; Mashudi (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
This article discusses the changes and developments in the political system in Indonesia after the reformation. The reformation brought significant changes in the distribution of power and the repositioning of a more democratic political system, including direct elections for regional heads and members of the DPR/DPRD and DPD. However, the implementation of a better system faces challenges, especially in understanding and utilizing the distribution of power at the local level, which is often accompanied by a culture of corruption. This article also highlights the role of society in promoting political stability through intergenerational mobility and how the Indonesian political system adapts to external and internal influences.